Quality Non-Gluten Flour as a Substitute for Wheat Flour in Making Steamed Brownies - Nuresa, Herlina Dwi; Prihatno; Nugroho, Setyo Prasiyono (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2022)
The purpose of this study is to see how respondents react to non-gluten flour-based steamed brownies in terms of taste, texture, scent, colour, and appearance compared to wheat flour-based steamed brownies. This study is quantitative in that the data analysis method used to test the hypothesis is a single classification variant analysis after the prerequisite tests, namely the homogeneity and normality tests, have been completed. The taste indicator results of the Anova test (significant value > 0.05 = 0.831 > 0.05) revealed no significant difference between wheat flour steamed brownies and steamed brownies with a combination of mocaf flour and soybean flour. According to the texture indicator (significance value > 0.05 = 0.311 > 0.05), there is no significant difference between wheat flour steamed brownies and steamed brownies with a combination of mocaf flour and soybean flour. According to the scent indicator (significant value > 0.05 = 0.513 > 0.05), there is no significant difference between wheat flour steamed brownies and steamed brownies with a combination of mocaf flour and soybean flour. According to the colour indicator (significant value > 0.05 = 0.069 > 0.05), there is no significant difference between wheat flour steamed brownies and steamed brownies with a combination of mocaf flour and soybean flour. Meanwhile, the appearance indicator indicates that there is (a significant value > 0.05 = 1.0 > 0.05), indicating no significant difference between wheat flour steamed brownies and steamed brownies with a combination of mocaf flour and soybean flour from the appearance indicator.